2019
DOI: 10.2174/1568026619666190603094439
|View full text |Cite
|
Sign up to set email alerts
|

New Promises to Cure Cancer and Other Genetic Diseases/Disorders: Epi-drugs Through Epigenetics

Abstract: All the heritable alterations in gene expression and chromatin structure due to chemical modifications that do not involve changes in the primary gene nucleotide sequence are referred to as epigenetics. DNA methylation, histone modifications, and non-coding RNAs are distinct types of epigenetic inheritance. Epigenetic patterns have been linked to the developmental stages, environmental exposure, and diet. Therapeutic strategies are now being developed to target human diseases such as cancer with mutations in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 147 publications
0
2
0
1
Order By: Relevance
“…Currently, the implication of epi-drugs still shows promising results in cancer clinics. [49][50][51] In this study, we attempted to test LPS-induced malignant transformation in prostate epithelial cells by utilizing multiple tools including stem-like tumorosphere forming assay. Indeed, treatment with lower dose of LPS (less than 0.02 μg/mL), rather than with higher dose of LPS, promoted the epithelial cell undergoing migration, invasion with down regulation of CK8/vimentin and CK18/vimentin (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the implication of epi-drugs still shows promising results in cancer clinics. [49][50][51] In this study, we attempted to test LPS-induced malignant transformation in prostate epithelial cells by utilizing multiple tools including stem-like tumorosphere forming assay. Indeed, treatment with lower dose of LPS (less than 0.02 μg/mL), rather than with higher dose of LPS, promoted the epithelial cell undergoing migration, invasion with down regulation of CK8/vimentin and CK18/vimentin (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…It has mild experimental neurotoxicity and the capacity to inhibit tubulin polymerization [9]. Studies have revealed the effectiveness of vindesine in treating pediatric acute lymphoblastic leukemia, chronic myelocytic leukemia, esophageal cancer, and non-Hodgkin's lymphoma [10]. In contrast, leurocristine is clinically administered to treat acute leukemia and other malignant tumors [11] and is a potential serious neurotoxin [12].…”
Section: Introductionmentioning
confidence: 99%
“…A reprogramação epigenética, a partir da utilização de epi-drogas desenvolvidas para esse fim, pode ser uma alternativa, podendo também, fazer parte de uma terapia combinada com outros fármacos, visando a eliminação da resistência ao agente quimioterápico e possibilitando sucesso terapêutico no combate aos carcinomas orais.1.3.Epigenética é a ciência que estuda as mudanças hereditárias na expressão gênica e na estrutura da cromatina devido a modificações químicas, sem alteração na sequência de nucleotídeos do DNA. Os padrões epigenéticos são associados a diversos fatores como estágios de desenvolvimento, exposição ambiental e dieta alimentar(DUAN et al, 2019). Essas modificações regulam a acessibilidade à cromatina, processo essencial ao desenvolvimento normal.…”
unclassified